Have Public Health Spending and Access in South Africa Become More Equitable Since the End of Apartheid? - Burger, Ronelle; Bredenkamp, Caryn; Grobler, Christelle; van der Berg, Servaas (Taylor and Francis, 2013)
This study investigates whether health spending and access to services in South Africa have become more or less pro-poor over time. We find that over the post-apartheid period health spending has become significantly more pro-poor. In addition to the rising share of the health budget allocated to public clinics, there has been an increase in the share of public clinic and hospital spending going to the poor and a rising share of the health budget allocated to public clinics. In addition, between 1993 and 2008 there were improvements in both financial access to public health services – as measured by the incidence of catastrophic costs – and physical access to public health facilities – as measured by reduced travel time. Given that substantial progress has been made with fiscal equity and access to health, problems that users complain about – rude staff, long queues and lack of medicine – have moved higher on the policy agenda.